Assessment of Bukavu Finalist Pupils' English Active Vocabulary Knowledge - TrÃ©sor, Mihigo Bienfait (Journal of English Education Program, 2024)
The Congolese national program of English instructs that secondary school pupils be equipped with 2,000 active words in the four years of English training (based on 500 active words per year), so that they can be able to communicate effectively in English. However, the Congolese State Exams do not evaluate finalist pupils"™ level of English active vocabulary knowledge to check whether this objective is reached or not. Consequently, the finalist pupils"™ actual level of English active vocabulary knowledge at the end of their secondary school education remains unknown. To have an idea on the level, this study aimed at assessing Bukavu finalist pupils"™ English active vocabulary knowledge. After a random sampling of 35 (10%) Bukavu secondary schools with the final year, the data were collected from 1506 Bukavu finalist pupils of the scholar year 2021/2022 through a test of English active vocabulary knowledge, which comprised multiple choice and traditional questions. The data, compiled in Excel for easy handling, showed the following English proficiency levels among Bukavu finalist pupils: below elementary 4.1%, elementary 69.9%, pre-intermediate 22.8%, intermediate 2.8%, upper-intermediate 0.4%, and advanced 0.0%. In summary, most pupils in Bukavu secondary schools end their English training with an "elementary level," possessing an average of 594 (29.7%) active words instead of the expected 2,000. Finally, relevant recommendations were made to the Congolese legislator, teachers of English and Bukavu secondary school pupils for the increase of the level.